교회현장에서 칼 로저스의 인간중심상담 적용에 관한 연구 - 방윤주(BANG Youn-Ju) (Changsin nondan, 2023)
칼 로저스는 인간에 대한 적극적인 이해를 바탕으로 내담자를 한 인격체로 대하며 무조건적인 수용적 태도를 지향한다는 점에서 최근 20세기에 자주 언급되는 심리학 학자이다. 이에 기독교 계통의 상담가들은 그의 이론에서 신학적인 유사점을 발견하고 그의 이론을 크게 환영하였다. 하지만 인본주의 심리학의 대표인 그의 인간이해와 상담이론은 기독교 심리학자들의 비판의 대상이 되기도 한다. 그럼에도 여전히 한국목회상담협회 사례 발표회를 참여해보면 로저스의 인간중심 상담을 주요 기법으로 채택했다는 상담가를 쉽게 발견할 수 있는 것이 현실이다. 실제 로저스의 상담이론을 보면 기독교 신학과 비슷한 면들이 많이 발견되어 지고 실제 예수님의 공생애 사역 현장에서도 발견되어 진다. 그러나 로저스의 이론은 어디까지나 인본주의 중심의 상담이론이기에 무조건적으로 수용하여 목회상담현장, 특히 교회 안에서 적용하기에는 한계가 있다. 겉으로 보이는 기독교 신학과의 유사한 점만을 강조하여 기독교상담이라고 이름 붙이는 것도 조심스러운 것이 현실이다. 그럼에도 성경적 가치관과 일맥상통하는 면을 선택적으로 잘 받아들이고 활용한다면 교회 안에서 성도들을 긍정적으로 변화시키는데 유용하게 사용될 수 있는 이론이 될 것이라 본다. 이에 연구자는 본 논문에서 로저스의 상담이론을 목회상담 현장, 그 중에서도 특히 교회 안에서 적용한다면 적용가능한 부분은 무엇이고 목회신학적 한계와 비평은 무엇인가를 살펴보려고 한다. 이를 통해 목회상담과 인간중심상담 사이에 존재하는 차이점을 인정하되 목회 현장에서 실천할 수 있는 인간중심상담의 긍정적인 측면을 활용하고 상담가(목회자)가 최소한의 내담자를 대하는 기본적인 상담 자세와 주의할 점을 훈련 받는다면 교회 현장 내에서 더 풍요로운 도움을 받을 수 있다고 본다. 또한 이러한 태도는 목회 상담가와 내담자가 함께 성장할 수 있는 좋은 기회가 될 수 있다고 본다. Carl Rogers is a psychologist frequently mentioned in the recent 20th century in that he treats his clients as a person based on a pro-active understanding of humans and aims for an unconditional receptive attitude. Accordingly, counselors from the Christian world found theological similarities in his theory and applauded his theory greatly. However, his understanding of human and counseling theory, which are the representative of humanist psychology, are also subject to criticism by Christian psychologists. Nevertheless, in reality, when one participates in the case presentations of the pastoral counseling association, one can easily find counselors who have adopted Rogers’ human-centered counseling as their main technique. Looking at Rogers’ counseling theory, one can easily find many aspects that are similar to Christian theology, and it is also found in the actual symbiotic ministry of Jesus. However there is a limit for an unconditional acceptance and application of Roger’s theory into the pastoral counseling practice, especially within the church, since it is a humanist-centered counseling theory. The reality is that it is also cautious to name it Christian counseling by emphasizing only on similarities with Christian theology. Nevertheless, if one selectively accepts and utilizes aspects that are in line with biblical values, it will be a theory that can be used to positively change the believers in the church. Therefore, in this paper, the researcher will look at what is applicable and what are the limitations and criticisms of pastoral theology if Rogers’ counseling theory is applied to the pastoral counseling field, especially within the church. Through this, the fundamental difference between pastoral counseling and human-centered counseling is recognized, but if counselors (ministers) are trained in basic counseling attitudes and precautions towards clients, clients can receive richer help in the church. In addition, this attitude can be a good opportunity for pastoral counselors and clients to grow together. KCI Citation Count: 0